P734 Feasibility and accuracy of the new automated software dynamic heart model in an unselected population. (17th January 2020) - Manfredonia, L; Fusini, L; Muratori, M; Tamborini, G; Gripari, P; Mantegazza, V; Volpato, V; Italiano, G; Lombardo, A; Crea, F; Pepi, M
Abstract: Objective: Preliminary studies showed the accuracy of machine learning based automated dynamic quantification of left ventricular (LV) and left atrial (LA) volumes. We aimed to evaluate the feasibility and accuracy of this new Dynamic Heart Model (DHM) software in an unselected population undergoing transthoracic echocardiography (TTE). Methods. We enrolled 91 consecutive unselected patients (80% in sinus rhythm) referred for clinically indicated 2D TTE, who also underwent single 3D TTE image acquisition from the apical 4-chamber view. 2D images were analyzed to measure ejection fraction, LV and LA volumes; 3D images were analyzed using Dynamic Heart Model (DHM) software (Philips Healthcare), which automatically measures chamber volumes throughout the cardiac cycle, resulting in LV and LA volume-time curves. Average time of analysis, feasibility, image quality were recorded and results compared between the 2D and 3D techniques. Results. Quality of the 91 2D TTE images was graded as poor (N = 13), satisfactory (N = 45) and good (N = 33). The use of DHM was feasible in 79/91 cases (87%). The remaining 12 datasets could not be analyzed because of poor images (N = 10) or incorrect automated border detection (N = 2): in these cases, the software did not accurately identify endocardial borders due to LV cavity near obliteration or extreme LA enlargement. When feasible, the boundary position was considered accurate in 61/79 patients (77%), while minor manual correction of the LV/LA borders was needed in the remaining cases. In only 1 case the reconstruction was considered unreliable because it needed major corrections. The overall time required to obtain DHM data was approximately 45 seconds. In all cases in which DHM was used, not only shapes of LV and LA were very well defined, but also functional curves were physiologically plausible. Even in the 13 patients in whom the 2D image was suboptimal, the DHM was not only feasible but also accurate endocardial boundaries in 8 cases, without (N = 5) or with only minimal manual corrections (N = 3). As expected, 3D LV volumes were slightly hige than 2D ones ( EDV 153.9 ± 59.8 vs 121.4 ± 47.3 mL, respectively), while LV EF and LA volumes were similar (EF 58.8 ± 11.8 vs 59 ± 11.8% and LA volume 92 ± 39.3 vs 83.4 ± 32.1 mL, respectively). Conclusions. The new DHM software is quick, feasible and accurate in the majority of unselected patients, including those with suboptimal 2D images or in atrial fibrillation. Introduction of this automated analysis into clinical practice can reduce examination time, while providing reliable information not only on volumes but also on function of the left heart chambers.